(untitled) (Journal of the College of Basic Education, 2023)
Education has an important role in strengthening the relationship between the youth and the environment and helping him to grow in the direction ofdesirable, the school as a social institution works through the educational process onAchieving and developing the goals that the society accepts at a specific time. :11 p.m. (5And the importance of school curricula as an “essential” element in the educational process and the means of education.and its content to achieve its objectives in the comprehensive growth of the learner and to build and modify his behavior in accordance with the philosophy ofsociety and its objectives. It was imperative for any educational system to build a “docical” curriculum. for a process to take placeBuilding curricula and developing them in a sound scientific way must be based on solid scientific foundations.Through tools characterized by honesty and objectivity, the textbook is not just a specific tool.Rather, the teaching itself is the specific lesson, and everything that is used in teaching is onlyThey are things affiliated with the textbook, helping students to understand, as it is an asset in the educational process.and not just a helper, especially in the primary stage, as the basis for the schoolElementary school is to provide all children, starting from the age of six, with education and culture.the two necessities to make them good citizens of sound body, mind and morals who believe in God and understandtheir national and human message, and they are loyal to their homeland, and it aims to discover their readinessand their talents, in order to direct them to what is appropriate to these aptitudes and talents, and to ensure their development and utilization.in their social, cultural and professional life, the curricula seek to provide learners withwith experiences that contribute to the growth of their activity and the formation and development of their concepts.The basic functions of education are the transfer of experiences and knowledge that humanity has reached over the years.eras to the present generations, educators have taken care to provide learners with the basic conceptsthat convey these experiences, including the huge amount of knowledge and information, as well as